The triple exponentially weighted moving average control chart. Issue 3 (4th May 2021) - Alevizakos, Vasileios; Chatterjee, Kashinath; Koukouvinos, Christos
ABSTRACT: Quality control charts are extensively used to monitor processes. The EWMA chart is a good alternative to the Shewhart chart to quickly detect small and moderate shifts in the process mean. The DEWMA charting procedure is an enhanced approach for the EWMA chart and performs much better, especially for small and moderate shifts. In this article, we propose the triple EWMA (TEWMA) chart in an effort to improve much more the detection ability of the classical EWMA chart. Monte Carlo simulations are used to evaluate the run-length characteristics of the proposed chart. A comparison study versus the DEWMA, EWMA and GWMA charts indicates that the TEWMA chart with time-varying control limits is more effective in detecting small shifts while it is comparable with the other charts in moderate and large shifts. Moreover, the proposed chart has better inertia properties than the competing charts and is also shown to be in-control robust for small values of the smoothing parameter. Finally, two examples are given to display the application of the TEWMA chart.